Kombinasi Senam Hipertensi dan Pemberian Jus Mentimun untuk Menurunkan Tekanan Darah Pada Penderita Hipertensi di Kota Palembang - Ardianty, Septi; Aryani, Iin; Amsal, Muhammad; Kopolino, Aldora Ramadhini; Andini, Andini; Septriana, Ida; Malahati, Nabila (Jurnal Pengabdian kepada Masyarakat (ABDIKEMAS), 2025)
Hypertension is a health problem that often goes undetected but carries the risk of serious complications. Hypertension management requires non-pharmacological interventions such as hypertension exercises and cucumber juice consumption. This community service activity was conducted in neighborhood association RT 61, 16 Ulu Village, Palembang, with the aim of helping lower blood pressure in hypertensive communities. The service included blood pressure checks before and after the intervention, hypertension exercises, and the administration of cucumber juice. Results showed a decrease in average systolic blood pressure from 165 mmHg to 148 mmHg and diastolic blood pressure from 88 mmHg to 80 mmHg after the intervention. This activity received a positive response from participants and encouraged them to continue the hypertension exercises and consume cucumber juice independently as an effort to control blood pressure and prevent hypertension complications in the community.